2021
DOI: 10.1007/s13520-021-00120-3
|View full text |Cite
|
Sign up to set email alerts
|

Why religiosity is not enough in workplace ethical decision-making

Abstract: Substantial literature has investigated the relationship between religiosity and ethical decision-making (the what), while lesser consideration has been given to exploring why decisions are made. As part of a larger study, this paper aims to delve beyond the descriptive relationship between religiosity and ethical decision-making of Muslim employees in Malaysia. We analyse the qualitative data received from 160 employees by using thematic analysis. Our results reveal that, while religious values are important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 85 publications
1
0
0
1
Order By: Relevance
“…This suggests that any change in religiosity will notably enhance Falah Welfare. These findings align with previous research, such as Sulaiman et al (2021), which also demonstrated a positive and significant correlation between religiosity and personal well-being. Additionally, other studies have highlighted the restorative benefits of religiosity in promoting societal prosperity (Cunningham, 2016;Umuri & Ibrahim, 2020).…”
Section: Religiosity Influence On Falah Welfaresupporting
confidence: 92%
“…This suggests that any change in religiosity will notably enhance Falah Welfare. These findings align with previous research, such as Sulaiman et al (2021), which also demonstrated a positive and significant correlation between religiosity and personal well-being. Additionally, other studies have highlighted the restorative benefits of religiosity in promoting societal prosperity (Cunningham, 2016;Umuri & Ibrahim, 2020).…”
Section: Religiosity Influence On Falah Welfaresupporting
confidence: 92%
“…In fact, the results of the current study are in consistence with the results of a number of previous studies in other countries, which concluded that teaching ethics did not have a significant impact on the ethical decisions of accounting students (Arfaoui et al, 2016;Buell, 2009;Gammie and Gammie, 2009;Rogers and Smith, 2008). Also, the findings of this study confirm the findings of Sulaiman et al (2021) and Montenegro and Rodrigues (2020), which revealed that, while religious values are important, there are other factors that are also pertinent when making decisions at work, namely, the organization's interest and the context of the decision. The results of this study are also consistent with the results of Ebaid (2021), which revealed that most of final year accounting students in Saudi universities, including Umm Al-Qura University, have indulged to varying degrees in academic dishonesty, as one of the unethical behaviors, which is considered an indication of the weak effect of teaching religious courses on students' perception of ethical behaviors.…”
Section: Ethics and Accounting Educationsupporting
confidence: 90%
“…Estos resultados se ven reflejados en Adi y Adawiyah (2018), al ser la religión una variable moderadora entre el marketing medioambiental y el rendimiento de las empresas en Indonesia. Otros estudios al respecto son los de Herzog y Beadle (2018) Sulaiman et al (2021) y Sulaiman et al (2021a). La religiosidad también está relacionada con la responsabilidad social corporativa en países emergentes (Zaman et al, 2018).…”
unclassified